(untitled) (Research, Society and Development, 2022)
The health and safety at work of the radiology technician is achieved through measures that cover adequate health requirements, adoption of standards, protocols and procedures consistent with radioprotection and compliance with legal provisions. In this sense, the objective of this research is to analyze the working conditions offered to the technical professional in radiology, with a focus on health and safety. The methodology applied had a qualitative approach with exploratory-descriptive objectives, including the participatory method. Data were collected from nine radiology technicians and two directors of hospital management in two public units in the city of Rolim de Moura - RO, using a questionnaire and hospital visits. Result: Of the radiology technicians participating in the study, 88.9% consider satisfactory compliance with the legal provisions that regulate the profession, regarding the adoption of standards and protocols aimed at quality, 61.1% are dissatisfied and the working conditions on the sanitary requirements 62.4% were unsatisfactory, not being adequate. There was a lack of several elements of health and safety, demonstrating an analogous scenario, as it encourages changes, implementation of improvements and professional development.